Comparative Evaluation of Liposomal and Crude Antigen Vaccines Against Avian Pathogenic Escherichia coli in Broiler Chickens - Ahmid Hamid Dawood Alatbee Alatbee; Ali A. Al-Iedani (Universitas Muhammadiyah Sidaorjo, 2026)
General Background: Avian pathogenic Escherichia coli (APEC) remains a major challenge in poultry production, necessitating reliable vaccination strategies. Specific Background: Liposomal and crude antigen vaccines represent distinct formulations with different capacities to stimulate humoral and cellular immune responses. Knowledge Gap: Comparative evidence on their immunogenic profiles in broiler chickens, particularly across key cytokine markers and IgY levels, remains limited. Aims: This study evaluated and compared the immunogenicity of liposome-based (LIPO) and crude antigen (CRU) vaccines against APEC in broiler chickens. Results: Both vaccines significantly increased IL-4, IL-10, IgY, IL-12, IL-1β, and IFN-γ compared to the control (p < 0.0001). LIPO vaccination induced higher IL-4, IgY, IL-12, IL-1β, and IFN-γ levels, indicating strong activation of both Th2-mediated humoral and Th1-mediated cellular responses. CRU vaccination showed increased IL-10 and moderate cytokine responses, suggesting partial immune activation. Novelty: This study provides a direct immunological comparison of liposomal and crude antigen formulations using multiple cytokine indicators in a controlled broiler model. Implications: The findings support liposomal vaccines as a promising strategy for inducing balanced immune responses against APEC, contributing to improved poultry health management and reduced reliance on antimicrobial interventions. Highlights:• Liposomal Formulation Induced Higher Cytokine and Antibody Responses Across Measured Markers• Crude Antigen Vaccine Showed Partial Activation With Elevated IL-10 Levels• Both Formulations Triggered Innate and Adaptive Immunity in Broiler Models Keywords: Liposomal Vaccine, Crude Antigen, Broiler Chickens, Humoral Immunity, Cellular Immunity.